Effect of smoking on patient-reported postoperative complications following minor oral surgical procedures - Alaa A. Sanari; Bushra A. Alsolami; Hala M. Abdel-Alim; Mohammed Y. Al-Ghamdi; Dalia E. Meisha (Saudi Dental Journal)
Objective: This study evaluated the effect of smoking on patient-reported postoperative complications after minor oral surgical procedures by comparing the post-extraction symptoms between smokers and nonsmokers. Materials and methods: Patients undergoing minor oral surgical procedures were recruited and followed up prospectively on the first, second, seventh, and twenty-first days after simple dental extractions. Results: A total of 85 patients completed the study. Postoperative pain, measured with a visual analog scale, was consistently higher among smokers than nonsmokers (P < 0.0001). Patient-reported experience of bleeding events was significantly less among nonsmokers (P = 0.009) only on the first postoperative day. Facial swelling was more common in smokers than in nonsmokers (P = 0.04) on the second postoperative day. Postoperative infection was reported more by smokers than nonsmokers (P > 0.05). Trismus did not vary with time according to smoking status. On the 21st postoperative day, there were no statistically significant differences in postoperative complications between the groups. Conclusions: The patient-reported pain score was consistently higher among smokers. The study’s findings suggested that initial differences in patient-reported complications between smokers and nonsmokers undergoing minor oral surgical procedures diminished after a week.